Các hợp chất thứ cấp từ chủng xạ khuẩn biển Micromonospora sp. (G043) - Tuấn, Cao Đức; Hiệu, Trần Văn; Mai Hương, Đoàn Thị; Quyên, Vũ Thị; Hồng Minh, Lê Thị; Murphy, Brian; Minh, Châu Văn; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2016)
Analysis of an antimicrobial extract prepared from culture broth of the marine-derived actinomycete Micromonospora sp. (strain G043) led to the isolation of 9 secondary metabolites and identified as Cyclo-(Pro-Leu) (1), Cyclo-(Pro-Val) (2), Cyclo-(Pro-Trp) (3), Cyclo-(Pro-Phe) (4), Cyclo-(Pro-Tyr) (5), and Cyclo-(Leu-Tyr) (6), 2-phenylacetic acid (7), N-(4-hydroxyphenylethyl)acetamide (8), bis(2-ethylhexyl) adipate (9). The structures of 1-9 were determined by analyses of MS and 2D NMR data. All compounds were evaluated for their antimicrobial activity against a panel of clinically significant microorganisms. Compounds 3, 6 and 7 inhibited Escherichia coli with a MIC value of 128, 32 and 32 µg/ml, respectively.